Issues of educational leadership - Aefsky, Fern, 1956- (London, Rowman & Littlefield, 2021)
"This book focuses on the need for school and organizational leaders to be able to lead others through a crisis, such as school and community shootings and unrest; pandemic issues; and weather-related emergencies"--
Keywords: School management and organization; Crisis management; Educational leadership